Corrosion damage detection in reinforced concrete using Rayleigh wave-based method - Cheng, Weixia (2024)
Corrosion of reinforcing bars is a dominant cause of degradation of reinforced concrete (RC) structures. Over time, expansive products of corrosion build up tensile stresses within the concrete, leading to cracks on the exterior surface and spalling of concrete cover. To extend the service life of RC structures, a reliable non-destructive inspection method is required to detect and evaluate corrosion-induced internal cracks in concrete before spalling, so that timely repair can be conducted. Ultrasonic Rayleigh waves have been employed to detect near-surface cracks in concrete based on their transmission coefficient in frequency domain or their time-of-flight information. However, due to heterogeneity of concrete materials, the ill-defined Rayleigh wave component and the sensor coupling on the rough surface of concrete have a significant influence on accuracy of the method. In this study, an improved method using Rayleigh waves has been investigated to detect corrosion-induced internal cracks in concrete. In the method, energy spectrum of the Rayleigh wave is analysed using the continuous wavelet transform and correlated to locations of internal cracks. This method is not sensitive to surface roughness of concrete members and does not need accurate identification of the Rayleigh wave components. Performance of the method was examined using corroded RC specimens with different cover depths and aggregate sizes. As a comparison, electrochemical tests were performed to map the corrosion current density. The test results showed very good agreement with the corrosion damage map generated from the proposed Rayleigh wave-based method.